(untitled) (Asian Journal of Medical and Biological Research, 2020)
The study was attempted to collect information on buffalo husbandry practices existing in household farming level along with farmers’ status and problems they faced with probable solutions in selected coastal regions of Bangladesh. Data were collected from eighty (80) randomly interviewed household farmers of two coastal districts (Bhola and Patuakhali) through questionnaire from 1st January to 30th June 2019. Buffalo rearing was practiced by male farmers (85%) in age group of 31-45 yrs (47.5%) having primary level education (51.25%) and belonged to small category of farmers (52.5%) whose main occupation is agriculture (76.25%). About 82.5% farmers used own capital while 96.25% farmers practiced buffalo rearing without any training. Majority (80%) of the farmers had small herd size (<6) where highest number (91.25%) of farmers kept female buffaloes. About three-forth farmers (77.5%) did not care for housing of their buffaloes. Among the sheds provided mainly at night (85%), most of them had tinned roof (91.25%), muddy floor (97.5%), inadequate floor space (70%) and improper drainage system (65%). Maximum farmers (90%) practiced grazing their buffaloes from morning to evening at public land and offered locally collected natural roughages at night but did not practice concentrate feeding. No farmers accepted any feeding technology, used vitamin-mineral supplements or growth promoters and followed balanced ration feeding to buffaloes. Clean drinking water supply (3.75%) was very poor practice although farmers had opportunity. Natural breeding (85%) was more prominent practice and buffaloes mainly showed heat in winter. About 45% and 60% farmers practiced irregular vaccination and de-worming, respectively. Feeds shortage is the most common problem along with others where attention is needed. The overall observations indicated that scientific management practices to exploit inherent capacity of buffaloes were not adopted by farmers and hence, management practices were not satisfactory and need to be corrected through motivation and providing extension services among farmers. Asian J. Med. Biol. Res. June 2020, 6(2): 255-264